The support of Romani children by the family in social integration - Piecuch, Ewelina (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The support of family is an important factor in stimulating the development of a young person. Due to this factor a Romani child strives to acquire new information about the world in which he or she lives. School is one of the places, in which the processes of learning and social integration take place. The state (in an attempt to encourage Romani families to participate in social-cultural life) created the “State Programme for the Romani Community in Poland”. As a part of this programme at the break of the year 2012/2013 I conducted integration workshop classes in public elementary schools in Wrocław. The children of the pre-school unit from the Polish and Romani communities participated in the classes. I have used the qualitative approach in the interpretative paradigm. I have used the method of research in action. I have presented the conclusions from the participative observation, which I have conducted in the group, researching the engagement of children in the classes, their interest in the topic, the interactions during the workshops, their attendance as well as the attitude of parents towards the classes.
Keywords: support; child; family; social integration; Romani people